Medical disorders in pregnancy and pregnancy outcome: a retrospective analysis - Shriastava, Sushruta; Malik, Nivedita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Medical disorders, including hypertensive diseases, diabetes, thyroid disorders may exist prior to pregnancy or may manifest themselves for the first time during pregnancy. Methods: This retrospective study was conducted at the Department of Obstetrics and Gynecology of tertiary care hospital by reviewing all medical records of pregnant patients with medical disorders admitted for delivery from January 2016 to December 2016. Data collected was analysed using simple statistical measures like percentage and proportion. Results: Most common medical disorder was pregnancy induced hypertension and its complication seen in 43% of the females; followed by anaemia and hypothyroidism seen in 20% females respectively. Maximum perinatal morbidity was seen in females suffering with hypertensive disorders (53.4%), with 17(41.8%) IUGR and 6 (11.6%) intra uterine demise respectively. Following PIH, higher rate of perinatal morbidity was seen in anaemic females (50% IUGR). Conclusions: A detailed history taking and evaluation of all pregnant females at the first visit, regular antenatal follow-ups, investigations will help us to detect the pre-existing medical disorders or the pregnancy associated medical disorders in time. If the condition is detected early, it is easy to treat with very little detrimental effects to the mother and foetus.